HUBUNGAN ANTARA POSTUR KERJA DENGAN KELUHAN MUSCULOSKELETAL DISORDERS PADA PEKERJA LAUNDRY DI KECAMATAN BATAM KOTA KOTA BATAM 2023 - Kasih Purwati; Andi Ipaljri Saputra; Arsenio Taolin (Universitas Batam, 2023)
Background: One of the jobs that is vulnerable to Musculoskeletal complaints is laundry workers. The most common occupational accidents are MSDs. Methods: This study is an observational analytical study with a cross-sectional approach on 97 laundry workers in batam city sub-district. Samples were selected using accidental sampling techniques. The data is the primary data from the questionnaire. Data analysis using univariate and bivariate analysis. Results: Based on the results of the chi-square correlation test, a p value of 0.016 (p < 0.05 was obtained). The p value from this data analysis obtained a value of 0.016 (p < α) so that it shows that there is a relationship between work posture and MSDs complaints in laundry workers in Batam City District. Conclusion: Based on the results of the chi-square correlation test, a p value of 0.016 (p < 0.05 was obtained). thus showing that there is a Relationship Between Work Posture and MSDs Complaints on Laundry Workers in Batam City District 2023.